2021
DOI: 10.1038/s41467-021-23895-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the link between molecular cloud ices and chondritic organic matter in laboratory

Abstract: Carbonaceous meteorites are fragments of asteroids rich in organic material. In the forming solar nebula, parent bodies may have accreted organic materials resulting from the evolution of icy grains observed in dense molecular clouds. The major issues of this scenario are the secondary processes having occurred on asteroids, which may have modified the accreted matter. Here, we explore the evolution of organic analogs of protostellar/protoplanetary disk material once accreted and submitted to aqueous alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 52 publications
(67 reference statements)
0
25
0
Order By: Relevance
“…This maturation effect has been shown to produce interesting self-organizational properties in glucose-ammonia reactions, 50 and has been noted recently in experimental molecular cloud analog maturation experiments. 51 …”
Section: Resultsmentioning
confidence: 99%
“…This maturation effect has been shown to produce interesting self-organizational properties in glucose-ammonia reactions, 50 and has been noted recently in experimental molecular cloud analog maturation experiments. 51 …”
Section: Resultsmentioning
confidence: 99%
“…In addition, in some specific CC meteorites, such as CI, CM, CR, and the ungrouped Tagish Lake (e.g., Pizzarello et al 2001;Pizzarello & Holmes 2009), the relative abundance of amino acids decreases with an increasing degree of aqueous alteration, indicating that this process altered the OM (Glavin et al 2010). Alternatively, aqueous alteration might also redistribute the initial molecular composition and allow the formation of new species (Vinogradoff et al 2017;Danger et al 2021). In contrast, thermal metamorphism has a more destructive effect on the OM and leads mainly to the graphitization and decrease of OM diversity (e.g., Kebukawa 2011).…”
Section: Chemical Evolution Of Water-rich Worldsmentioning
confidence: 99%
“…Laboratory studies have also shown that organic molecules (e.g., tholins, chondritic organics) are transformed in aqueous alteration experiments (Kebukawa et al 2013(Kebukawa et al , 2020Brassé et al 2017;Vinogradoff et al 2018;Danger et al 2021), producing numerous new soluble molecules and insoluble OM as a function of time and temperature. The nature and extent of OM evolution likely depends on the nature of the initial molecules, the interaction with minerals, and the fluid properties (Gil-Lozano et al 2020;Haas et al 2020;Vinogradoff et al 2020).…”
Section: Chemical Evolution Of Water-rich Worldsmentioning
confidence: 99%
“…The interstellar medium witnesses many astrophysical events including meteorite impacts with celestial bodies. Studies showed that a significant portion of soluble organic matter observed in carbonaceous meteorites can indeed originate from organic ices, derived from dense molecular clouds (Danger et al, 2021). For example, laboratory impact experiments showed that glycolaldehyde found in the ISM, as well as glycolaldehyde mixed with montmorillonite clay, when subjected to reverberated shocks (~5 to >25 GPa), resulted in the formation of a mixture of important biologically significant molecules such as ethylene glycol, threose, and erythrose (McCaffrey et al, 2014).…”
Section: Methanol a Key Synthon Toward Complex Organic Moleculesmentioning
confidence: 99%